An unavoidable modulation? Sensory attention and human primary motor cortex excitability. (19th June 2014) - Ruge, Diane; Muggleton, Neil; Hoad, Damon; Caronni, Antonio; Rothwell, John C.
Abstract The link between basic physiology and its modulation by cognitive states, such as attention, is poorly understood. A significant association becomes apparent when patients with movement disorders describe experiences with changing their attention focus and the fundamental effect that this has on their motor symptoms. Moreover, frequently used mental strategies for treating such patients, e.g. with task‐specific dystonia, widely lack laboratory‐based knowledge about physiological mechanisms. In this largely unexplored field, we looked at how the locus of attention, when it changed between internal (locus hand) and external (visual target), influenced excitability in the primary motor cortex (M1) in healthy humans. Intriguingly, both internal and external attention had the capacity to change M1 excitability. Both led to a reduced stimulation‐induced GABA‐related inhibition and a change in motor evoked potential size, i.e. an overall increased M1 excitability. These previously unreported findings indicated: (i) that cognitive state differentially interacted with M1 physiology, (ii) that our view of distraction (attention locus shifted towards external or distant location), which is used as a prevention or management strategy for use‐dependent motor disorders, is too simple and currently unsupported for clinical application, and (iii) the physiological state reached through attention modulation represents an alternative explanation for frequently reported electrophysiology findings in neuropsychiatric disorders, such as an aberrant inhibition.